Early Stage Oropharyngeal Carcinomas: Comparing Quality of Life for Different Treatment Modalities. (25th February 2014) - Ryzek, Don-Felix; Mantsopoulos, Konstantinos; Künzel, Julian; Grundtner, Philipp; Zenk, Johannes; Iro, Heinrich; Psychogios, Georgios
Abstract : Objective . To compare long-term quality of life outcomes after treating early stage oropharyngeal carcinoma either with surgery, surgery combined with radiotherapy, or surgery combined with chemoradiotherapy. Methods . Questionnaire based method: 111 eligible patients agreed to fill out a quality of life questionnaire. Results . Of the 32 scales contained in the EORTC's combined QLQ-C30 and HN35, 11 scales show significantly better results for the surgery-only treatment group when compared to either surgery combined with radiotherapy or surgery combined with any type of adjuvant therapy. These eleven scales are role function (P = 0.019/0.008 ), social function (P = 0.01/0.034 ), nausea (P = 0.017/0.025 ), pain (P = 0.014/0.023 ), financial problems (P = 0.030/0.012 ), speech (P = 0.02/0.015 ), social eating (P = 0.003 /<0.001), mouth opening (P = 0.033/0.016 ), sticky saliva (P = 0.001 /<0.001), swallowing (P < 0.001 /<0.001), and dry mouth (P < 0.001/0.001 ). Conclusion . Treatment of early stage oropharyngeal carcinoma with surgery alone has definite advantages over treatments including any form of adjuvant therapy when considering quality of life. Advantages manifest themselves especially in functional aspects of the head and neck realm; however general health aspects as well as psychosocial aspects show improvements as well. This study does not show any indication of QOL-related drawbacks of surgery-only treatment approaches.